STRUCTURE DESIGN OF FATMAWATI CITY CENTER JAKARTA APARTMENT - JOSHUA - NIM 15014081 , LEVI
This last assignment discusses about structure design of buildings. The buildings are designed for being used for settlement/apartment that have 27 level of stories, for each tower, with 85.5 m in height and also 4 level of basements with 12 m in depth. These buildings are designed using codes that are applied in Indonesia. Based on SNI 1726:2012, these buildings are categorized as Seismic Design Category D (SDC D) according to soil condition dan seismic spectral design acceleration at the site of the buildings. The buildings are designed to be resistant to an earthquake. With some consideration there are two structure system that being reviewed which is Special Moment Frame (SMF) and Dual System earthquake-resistant that consist of Special Moment Frame (SMF) with Special Structural Wall (SSW). ETABS software is used for structural modeling in this project with spectrum analysis for the earthquake analysis procedure. Modeling and structural analysis are based on SNI 1726:2012. Structural element designs, both cross section and reinforcement, are based on SNI 2847:2013 for beams, columns, slabs, and shear-walls. Columns and shear-walls are designed with PCACOL software to obtain the interaction (axial-moment) diagram. Design of slab is done using SAFE and ETABS software.